Floating catalyst chemical vapor deposition method of synthesizing carbon nanotubes and carbon nanofibers-CVD. - Ahmadun, Fakhru'l-Razi; Ali Atieh, Lmuataz; Al-Khatib, Maan Fahmai; Iyuke, Sunny Esayebbemu (2004)

(untitled)
This invention relates to a method of producing a carbon nanotubes (CNTs) and carbon nanofibers (CNFs), and more particularly, to a method of producing carbon nanotubes and carbon nanofibers using floating catalysts Chemical Vapor Deposition (CVD). According to the present invention, benzene gas is used as a carbon source for the synthesis of CNTs and CNFs under chemical vapor deposition conditions at a reaction temperature range from about 600 to 1200. A vaporized floating catalyst, ferrocene is used as a catalyst precursor for the growth of CNTs and CNFs. The present invention provides higher yield of CNTs and CNFs method with minimum purification steps. Therefore, the invention may be used to provide an inexpensive method for the mass production of CNTs and CNFs with purity of nearly 100%.